(untitled) (Research, Society and Development, 2022)
Objective: The objective of this study is to establish the role of metalloproteinases (MMPs) and the importance of their inhibitors in development. Methodology: This review was carried out with an exhaustive search strategy of scientific literature using PUBMED, ScienceDirect and Scielo as databases, using “Metalloproteinases”, “MMPs” and “Dental adesão” as keywords, and connectors such as “e”. Results: During bonding to dentin, it is beneficial to apply MMP inhibitors capable of not inhibiting dentin collagen breakdown in hybrid beds, improving bond strength to dentin, but also preventing secondary lesions. Conclusion: During dentin collagen, it would be beneficial to apply MMP inhibitors capable of not only inhibiting dentin collagen breakdown in hybrid layers, as well as improving dentin bond strength, but also preventing secondary caries around the restoration. The metalloproteinases play an important role in the administration, however, compounds such as chlorhexidine, as studied, have not been shown to improve the administration for a long period of time, on the contrary to doxycycline, whose studies support a better administration over a long period of time.